MXene‐Based Nanomaterials for Biomedical Applications: Healthier Substitute Materials for the Future. Issue 1 (4th December 2022) - Siwal, Samarjeet Singh; Kaur, Harjot; Chauhan, Gunjan; Thakur, Vijay Kumar
Abstract : MXene‐based nanomaterial is a revolution 2D material achieving outstanding scientific attention owing to its universal characteristics for different applications (such as electronic appliances, power production, sensors, drug transfer, and biomedical). Although, the cytotoxic consequences of MXene have a considerable circumstance. Thus, rigorous investigation of the biocompatibility of MXene is a crucial prerequisite, formerly the preface to the human biological approach. Literature reveals functional outcomes wherever MXenes are used in vitro and in vivo cancer representatives. It affects drug transfer methods, sensoring electrodes, and assisting mechanisms for photothermal treatment and hyperthermy techniques. In this review, the synthesis process (such as top‐down and bottom‐up approaches) and properties (such as mechanical, electrical, optical, oxidative/thermal stability, and magnetic) of MXene‐based nanomaterials (NMs) are discussed. In addition, the different applications (such as tissue engineering, cancer theranostic, and other biomedical [such as drug delivery biosensors and surface‐enhanced Raman spectroscopy substrates for biomedical applications], antiviral, and immunomodulatory properties against SARS‐CoV‐2) of MXene‐based NMs are discussed in detail. Finally, the conclusion, existing challenges, and future outlooks are highlighted for more scope in this field. Abstract : Herein, the synthesis process (top‐down and bottom‐up) and properties (mechanical, electrical, optical, thermal, and magnetic) of the MXene‐based nanomaterials (NMs) is described. Further, the different applications (such as tissue engineering, cancer theranostic, and other biomedical [such as drug delivery biosensors and surface‐enhanced Raman spectroscopy substrates], antiviral, and immunomodulatory properties against SARS‐CoV‐2) of MXene‐based NMs are presented in detail.